Carrier transport and recombination dynamics of InAs/GaAs sub-monolayer quantum dot near infrared photodetector. (4th October 2019) - Mukherjee, S; Mukherjee, S; Pradhan, A; Maitra, T; Sengupta, S; Chakrabarti, S; Nayak, A; Bhunia, S
Abstract: Here, we present a relative study of tunnel-induced photocarrier escape processes in a laterally coupled InAs sub-monolayer quantum dot-based photodetector (SML QD-PD) as a function of fractional coverage from 0.4 ML to 0.8 ML. Both by simulation and experiment, we have quantitatively described the temperature dependent interband photoresponse spectrally tuned in the near infrared region (835 nm–890 nm) on the basis of mutual competition between the interband carrier recombination and interdot tunneling lifetime with varying SML coverage. The progressively increasing recombination lifetime and decreasing interdot tunneling lifetime with increasing SML coverage has attributed to a faster photoresponse and greater responsivity. At higher coverage fraction, tunnel induced fast speed photocarrier transit through lateral array of SML QDs has been found to be capable of offering a faster temporal response (100 µ s) with faithful reproducibility up to higher frequencies (1.3 KHz). Here, we report a powerful strategy to simultaneously tune responsivity, speed of time response and detectivity by externally controlling the SML coverage. This time response is measured to be nine times faster than a conventional SK QD photodetector. With increased coverage, inhibition of dark current due to trapping of injected charge carriers up to higher temperatures have resulted in high sustainable photodetectivity of 8  ×  10 11 cm Hz 1/2 w −1 at ~250 K that offers near room temperature photodetection.